1981. Real-World Data on Safety and Effectiveness of Glecaprevir/Pibrentasvir for the Treatment of Patients With Chronic Hepatitis C Virus Infection on Opioid Substitution Therapy: Latest Results from the German Hepatitis C-Registry. (26th November 2018) - Reimer, Jens; Stoehr, Albrecht; Naumann, Uwe; Teuber, Gerlinde; Zamani, Carsten; Mauss, Stefan; Qurishi, Nazifa; Lohmann, Kristina; Kleine, Henning; Pangerl, Andreas; Christensen, Stefan
Abstract: Background: The coformulated direct-acting antivirals glecaprevir/pibrentasvir (G/P) are approved to treat chronic hepatitis C virus (HCV) genotype 1–6 infection. In clinical trials, G/P demonstrated high efficacy, but real-world data in patients on opioid substitution therapy (OST), a population for which antiviral treatment is critical for HCV elimination, are limited. Here we report the first real-world data on the effectiveness and safety of G/P for OST patients within the German Hepatitis C-Registry (DHC-R). Methods: The DHC-R is an ongoing, noninterventional, multicenter, prospective, monitored registry study. Data were collected between July 28, 2017 and February 9, 2018 from 104 sites in Germany. The analysis included adult HCV-infected patients who were treated with G/P according to the European Medicines Agency label. The primary endpoint was sustained virologic response at post-treatment week 12 (SVR12). Safety and tolerability were assessed in patients that completed treatment. Results: As of February 9, 2018, 638 patients had initiated on-label treatment with G/P and are included in the baseline analysis. Patients on OST comprised 26% (168/638) of the baseline population, of which most patients were treatment-naive, without cirrhosis and had HCV genotype 1a or 3. Among patients with available SVR12 data, 96% (27/28) of OST patients and 97% (66/68) of non-OST patients achieved SVR12. There were no virologic failures: of three early discontinuations, one OST patient was lost to follow-up and two non-OST patients discontinued treatment due to adverse events (AE). In the modified intention-to-treat population which excluded non-virologic failures, SVR12 was 100% for both OST and non-OST patients. The safety population included 321 patients in total. Among OST patients, 2% (2/84) experienced serious AEs (SAE) without any treatment discontinuations due to AE/SAE. Conclusion: In this real-world analysis, G/P treatment yielded favorable effectiveness and safety results in patients on OST. Updated data and SVR12 results will be presented. Disclosures: J. Reimer, AbbVie, Bristol-Myers Squibb, Gilead, Janssen-Cilag, MSD: Board Member and Scientific Advisor, Educational grant and Speaker honorarium. A. Stoehr, AbbVie, Gilead, Janssen, MSD, ViiV: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium. U. Naumann, AbbVie, Bristol-Myers Squibb, Gilead Sciences, Janssen, Mundipharma, MSD, Roche, ViiV: Board Member, Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium. G. Teuber, : AbbVie, BMS, Janssen, Gilead, MSD: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium. C. Zamani, AbbVie Inc.: Board Member and Scientific Advisor, Consulting fee. S. Mauss, AbbVie, Gilead, Falk, Janssen, MSD: Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium. N. Qurishi, AbbVie, Gilead, Janssen, MSD, ViiV, Mundipharma, Hexal: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium. K. Lohmann, AbbVie Inc.: Employee and Shareholder, Salary and Stock and/or options. H. Kleine, AbbVie Inc.: Employee and Shareholder, Salary and Stock and/or options. A. Pangerl, AbbVie Inc.: Employee and Shareholder, Salary and Stock and/or options. S. Christensen, AbbVie, Gilead, Indivior, Janssen-Cilag, MSD, ViiV: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium.